Russian fuel and energy complex modernization in the circular economy direction - V. Ya. Afanasiev; O. I. Bolshakova; A. A. Romantsov (Вестник университета)
The article discusses promising areas that contribute to the formation of a closed-cycle economy or, in other words, a circular economy in the Russian fuel and energy complex. The basic principles of the circular economy model aimed at preserving the environment through the transition from linear business models to more closedones and by increasing the efficiency of natural resources use have been outlined. The data on the estimates of the negative impact combustion of associated petroleum gas have been presented, the methods of its rational utilization and further use as raw materials for high-grade products have been analyzed. The petrochemical complex is presented as one of the fundamental elements of the circular economy. The advantages of using biogas as a supplement and alternative to fossil natural gas when moving towards a circular economy have been substantiated. The importance of implementing biogas projects in Russia in modern conditions has been emphasized. Factors’ number of constraining the development pace of the circular economy in the fuel and energy complex sectors have been identified. The key support measures and stimulation of companies by the state have been outlined.